(Un)used and (un)usable? The role of indicators in local decision-making. A Brazilian case study. (November 2015) - Maiello, Antonella; de Paiva Britto, Ana Lucia Nogueira; Mello, Yasmim Ribeiro; de Oliveira Barbosa, Paula Sousa
Highlights: Our research analyses the role of data/indicators for local water and sanitation decision-making. We investigated this problem empirically in Rio de Janeiro Metropolitan Area. Using a triangulation approach we combined qualitative and quantitative data. Findings showed that local governors do not use indicators to make decisions. Usability gaps and bridges are identified for future local governance design. Abstract: Data and indicators represent a fundamental tool for knowledge-based policies. They are usually produced by agencies operating at the national or supra national level. However, water and sanitation policies are implemented at the local level. Our article addresses the question of data and indicator usability at the municipal level, while investigating water supply and sanitation services. Firstly, we selected a sample of municipalities in the Rio de Janeiro Metropolitan Area and classified them according to a set of national indicators. Then, we interviewed the person responsible for water and sanitation policies in each municipality. By triangulating qualitative and quantitative data, we found gaps between the indicators produced by national information systems and the data required and employed by local decision-makers. Discussing these results in relation to the literature, we identified gaps and bridges, which could serve as key elements for a governance design baseline with the power to guide future local decision-making processes.